2012
DOI: 10.1038/onc.2011.579
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SHIP-1 protein expression in high-risk myelodysplastic syndromes is associated with miR-210 and miR-155

Abstract: The myelodysplastic syndromes (MDSs) comprise a group of disorders characterized by multistage progression from cytopenias to acute myeloid leukemia (AML). They display exaggerated apoptosis in early stages, but lose this behavior during evolution to AML. The molecular basis for loss of apoptosis is unknown. To investigate this critical event, we analyzed phosphatidylinositol (PI) 3 0 kinase signaling, implicated as a critical pathway of cell survival control in epithelial and hematological malignancies. PI 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…PTEN has been shown to be downregulated in high-risk MDS patients [22,23]. These findings along with the results of the present study indicate that miR-205-5p may contribute to MDS via a miR-205/PTEN/Akt signaling pathway.…”
Section: Discussionsupporting
confidence: 64%
“…PTEN has been shown to be downregulated in high-risk MDS patients [22,23]. These findings along with the results of the present study indicate that miR-205-5p may contribute to MDS via a miR-205/PTEN/Akt signaling pathway.…”
Section: Discussionsupporting
confidence: 64%
“…PTEN is a well-known tumor suppressor gene through its phosphatase protein product action (48). SHIP-1 and PTEN have been reported previously as the targets of miR-155 (26,49) and miR-21 (20), respectively. The present study confirmed that miR-155 and miR-21 target these two essential molecules accordingly during the induction of functional MDSC.…”
Section: Discussionmentioning
confidence: 99%
“…12,45,47 These evidences have motivated the development of anti-miR-155 drugs as potential anticancer therapeutics. 43,[48][49][50] Our data indicate that the oncogenic activity of miR-155 is cell context dependent, and thus suggest some caution before applying anti-miR-155 treatments to cancer patients.…”
Section: Discussionmentioning
confidence: 99%